非洲法语为母语汉语学习者对汉语可能补语形的掌握情况观察——以刚果（布）为例 - Mabiala Roland Naguydem (Faculty of Cultural Sciences, Universitas Sebelas Maret, 2025)
This paper takes the existing teaching model of high schools in Congo-Brazzaville as a case study with the aim of identifying potential areas for improvement, with a view to optimising the potential complement form, which is a feature of native Chinese grammar teaching in Congo-Brazzaville. Through an empirical analysis of Chinese Congolese learners in Congo, it was observed that they were able to master the possible complement structures of affirmative “V+de+C”, negative’V+not+C” and interrogative “V+de+C+V+not+C/V+de+C?”. The empirical analyses were conducted, and the following conclusions were drawn: (1) the students demonstrated a good grasp of “V+de+C”; (2) the students demonstrated a limited grasp of “V+not+C”; (3) the students demonstrated a lack of grasp of “V+de+C+V+not+C/V+de+C?”; and (4) the students demonstrated a reliance on the optative verb “neng”. The results of the study may be of interest to those involved in the teaching of potential complement to African native French-speaking Chinese learners, as they could inform the teaching of these knowledge in a positive way.